Temporary Immersion Bioreactor for In Vitro Multiplication of Raspberry (Rubus idaeus L.) - Bruno Reyes-Beristain; Eucario Mancilla-Álvarez; José Abel López-Buenfil; Jericó Jabín Bello-Bello (Horticulturae)
Raspberry (Rubus idaeus L.) micropropagation is an alternative for obtaining plantlets with high genetic and phytosanitary quality. The objective of this study was to establish a protocol for the micropropagation of raspberry (Rubus idaeus L.) using the temporary immersion bioreactor, under intermittent immersion periods and different culture medium volumes. The effect of the liquid medium using the TIB and semisolid was evaluated. Different immersion frequencies and culture medium volumes per explant were evaluated in the TIB. In all treatments, the number of shoots per explant, shoot length, number of leaves per explant, percentage of hyperhydricity, and chlorophyll and β-carotene content at multiplication stage were evaluated. The generated shoots, without a root system, were transferred to the acclimatization stage. The results show that the TIB with an immersion frequency of 2 min every 8 h and a volume of 25 mL of culture medium per explant had the best developmental parameters, with 5.75 shoots per explant, a shoot length of 3.44 cm, and 2% hyperhydricity. The highest chlorophyll and β-carotene content was observed in the TIB at different immersion frequencies of 4, 8 and 12 h, with 25 and 50 mL per explant. Survival percentages higher than 96% were observed in all methods evaluated. In conclusion, the evaluated immersion system is an efficient alternative for R. idaeus micropropagation, without using a rooting stage.